Math, asked by riddhima1806, 11 months ago

(sina-coseca)^2 +(cosa-seca)^2 = tan2a + cot2A - 1

Answers

Answered by spiderman2019
3

Answer:

Step-by-step explanation:

(SinA - CosecA)² +(CosA - SecA)²

= Sin²A+ Cosec²A - 2SinACosecA + Cos²A + Sec²A - 2CosASecA

= (Sin²A + Cos²A) + Cosec²A + Sec²A - 4

= Cosec²A + Sec²A - 3

= (Cosec²A - 1) + (Sec²A - 1) - 1

= Cot²A + Tan²A - 1

=  R.H.S

Hence Proved.

Answered by aryan5532
0

Answer:

pls get me the brainliest

Step-by-step explanation:(sinA-cosecA)^{2}+(cosA-secA)^2=sin^2A+Cosec^2A+cos^2A+sec^2A-2sinAcosecA-2cosAsecA

=(sin^2A+cos^2A)+cosec^2A+sec^2A-2sinA\frac{1}{sinA}-2cosA\frac{1}{cosA}

=1+cosec^2A+sec^2A-2-2\\=cosec^2A+sec^2A-3

=(cosec^2A-1)+(sec^2A-1)-1

=(cot^2A)+(tan^2A)-1\\=tan^2A+cot^2A-1

Hence,proved

Similar questions